Alternative Lithographic Technologies 2009
DOI: 10.1117/12.814188
|View full text |Cite
|
Sign up to set email alerts
|

Assumptions and trade-offs of extreme ultraviolet optics contamination modeling

Abstract: Extreme ultraviolet (EUV) lithography is one of the most promising candidates for device patterning at the 22 nm halfpitch node. The contamination of extreme ultraviolet optics has consistently been listed among the top challenges for the commercialization of EUV lithography. In a lithography exposure tool under radiation exposure, the two main mechanisms that degrade reflectivity of EUV molybdenum/silicon multilayer optics are carbonization and oxidation. The accumulation of carbon on the mirror surfaces is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…We found that the low-wavelength rate is approximately 4 times lower than the in-band rate over the pressure range (10 -8 to 10 -6 ) mbar. This trend of increasing contamination rate with wavelength is consistent with independent measurements 18 and calculations 19 . The wavelength dependence of other factors affecting the scaling behavior of contamination rates such as photon-stimulated desorption rates and intensity saturation are not known.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the low-wavelength rate is approximately 4 times lower than the in-band rate over the pressure range (10 -8 to 10 -6 ) mbar. This trend of increasing contamination rate with wavelength is consistent with independent measurements 18 and calculations 19 . The wavelength dependence of other factors affecting the scaling behavior of contamination rates such as photon-stimulated desorption rates and intensity saturation are not known.…”
Section: Discussionsupporting
confidence: 90%
“…The general trend of increasing contamination rate with wavelength in the rage (10 to 80) nm has been observed experimentally 18 and predicted by models 19 . A likely explanation of this behavior is that both the (gas phase) photoadsorption cross section and the secondary electron yield for C increase to a maximum around 70 nm.…”
Section: Wavelength Scalingmentioning
confidence: 82%
“…Contamination of EUV optics by the interaction of radiation with residual hydrocarbons is still one of the major concerns with EUV exposure tools [1][2][3][4][5][6][7][8] . It is well known that the carbonaceous contamination on the surfaces of EUV mirrors is caused only in the region of the mirror exposed to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…
Optics contamination remains one of the challenges in extreme ultraviolet (EUV) lithography [1][2][3][4][5][6][7][8] . Dependence of contamination rates on key EUV parameters was investigated.
…”
mentioning
confidence: 99%
“…Theoretical investigations were also carried out concerning the nonlinearity. 5,[10][11][12] We have studied contamination protection for surface oxidation 9,13) and carbon thin-film growth 14) using a highintensity undulator light source. We found that the nonlinear behavior of contamination growth is observed many times, such as the dependence of the decrease in reflectivity per unit dose of multilayer mirrors on EUV irradiance or the reflectivity distribution of doughnut shape, namely, high at the irradiation center, low in the surrounding area, and high in the non-irradiated area.…”
Section: Introductionmentioning
confidence: 99%